Annual review of comparative and international education 2021. volume 42, part B - Wiseman, Alexander W. (Emerald Publishing Limited, 2022)
Since 2013, the Annual Review of Comparative and International Education has covered significant developments in the intersecting fields of comparative education, international education, and comparative and international education. The Annual Review of Comparative and International Education 2021, Part B, begins with several chapters exploring conceptual and methodological developments in comparative and international education, followed by studies exploring research-to-practice, and new developments in comparative and international education. Topics covered in this volume include major theoretical and methodological developments such as critical realism, the effects of the coronavirus pandemic, and an exploration of white diaspora, anti-blackness and universities in the Global South; research-to-practice reports on education in emergency settings, surveillance studies, the needs of refugee and immigrant students; and new developments involving the internationalisation of community college careers, and educator acculturation in overseas schools. With contributions from leading scholars and professionals across the field of comparative and international education, this edition will be of use to education researchers and professionals alike.
Keywords: Comparative education.; International education.; Education -- Comparative.; Educational strategies & policy.; elektronické knihy; electronic books